TANTANGAN BANK SYARIAH DALAM MENINGKATKAN DAYA SAING DI TENGAH PERSAINGAN BANK KONVENSIONAL - Sartiyah, Sartiyah; Sugito, Asep; Supena, Supena (STIE Miftahul Huda, 2025)
ABSTRACT As more people become aware of the importance of sharia principles in financial transactions, sharia banking is expanding in Indonesia. However, in the face of fierce competition from conventional banks, Islamic banks encounter certain obstacles in their efforts to become more competitive. The purpose of this study is to pinpoint the difficulties Islamic banks encounter and create workable plans to boost their competitiveness. Using a qualitative methodology, this study analyzes relevant documents and conducts in-depth interviews with participants in the conventional and sharia banking sectors. According to the study's findings, Islamic banks confront significant obstacles because of their limited product offerings, inadequate technology, and the general public's ignorance of the Islamic banking system. Islamic banks must therefore put plans into place that emphasize the growth of human resources (HR), the use of digital technologies, product innovation, and public education.